2017
DOI: 10.3762/bjnano.8.177
|View full text |Cite
|
Sign up to set email alerts
|

Nanotribological behavior of deep cryogenically treated martensitic stainless steel

Abstract: Cryogenic treatments are increasingly used to improve the wear resistance of various steel alloys by means of transformation of retained austenite, deformation of virgin martensite and carbide refinement. In this work the nanotribological behavior and mechanical properties at the nano-scale of cryogenically and conventionally treated AISI 420 martensitic stainless steel were evaluated. Conventionally treated specimens were subjected to quenching and annealing, while the deep cryogenically treated samples were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Deep cryogenic treatment (DCT) is a sub-zero treatment where materials are exposed to temperatures below −125 • C with liquid nitrogen being the preferred cooling media [1]. Deep cryogenic treatment on martensitic steels is commercially carried out to improve wear resistance [2][3][4][5][6][7], and it has also been reported to affect other material properties such as hardness [8][9][10][11][12][13][14][15][16][17][18][19][20] and tensile strength [21][22][23]. There are some proposed mechanisms for these improvements in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Deep cryogenic treatment (DCT) is a sub-zero treatment where materials are exposed to temperatures below −125 • C with liquid nitrogen being the preferred cooling media [1]. Deep cryogenic treatment on martensitic steels is commercially carried out to improve wear resistance [2][3][4][5][6][7], and it has also been reported to affect other material properties such as hardness [8][9][10][11][12][13][14][15][16][17][18][19][20] and tensile strength [21][22][23]. There are some proposed mechanisms for these improvements in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…They are responsible for decreasing the friction and acts only marginally to decrease the wear coefficient [38].…”
Section: Except Of Few Data Points Identified At Lower and Upper Pormentioning
confidence: 99%
“…There is a large existing body of work on the tribological and wear properties of AISI 420 stainless steel [8,9,10,11,12,13,14,15,16,17]. Recently, D’Ans et al [8] studied the tribological and wear behaviors of the AISI 420/Fe 2 B surface layer by ball-disc tribological and wear tests.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, D’Ans et al [8] studied the tribological and wear behaviors of the AISI 420/Fe 2 B surface layer by ball-disc tribological and wear tests. For cryogenically-treated AISI 420 steel, Prieto et al [9,10] performed frictional wear tests with grease lubrication and an argon atmosphere. They found that the wear resistance of the cryogenically-treated specimen was enhanced by ~30–90%, compared to that of the conventionally-treated specimen.…”
Section: Introductionmentioning
confidence: 99%